Extreme probability analysis of drought periods in monsoon in relation to water need of crop stages - RAO, G. RAMAKRISHNA; PHULARI, D. G. (MAUSAM, 1984)
Extreme probability analysis of drought periods were conducted on daily rainfall from 1944 to 1976 for the frequencies 7, 10, 15, 20 and 25 days to adjust crop phases according to their water need. The study indicated that the first, fortnight of June, second fortnight of July, first fortnight of August and second fortnight of September are not suitable for .sowing, flowering and pod formation, panicle initiation, earhead emergence and grain filling of kharif crops respectively. If the crop phases are adjusted as per their water need with the available depth of rainfall three years of very successful "'cropping, five years with success and the crops may undergo severe moisture stress in, two year period. Further, the study reveals that if proper crop sequence is chosen the crops would have good harvest in a year particularly where the soil depth exceeds a metre.